A fresh approach to equine thoracic radiography. Issue 10 (15th November 2013) - Dunkel, Bettina; Gibbs, Christine; Weller, Renate
Abstract : Equine thoracic radiography is an important diagnostic tool for the evaluation of intrathoracic disease processes. Traditionally, the description of equine pulmonary radiographs has been based on the presence or absence of certain pulmonary patterns, namely bronchial, interstitial, alveolar and vascular patterns that are commonly used in other species. However, the use of these patterns is not always intuitive or suitable in horses and rarely helps in establishing a differential diagnosis for an individual case. This article sets out a simple, step‐by‐step approach for the evaluation of equine thoracic radiographs, which can be used to establish likely differential diagnoses. The assessment is based on the presence or absence and localisation of radiographic opacities that are easily recognised even by minimally trained observers. The article also describes radiographic technique in adult horses and foals, as well as discussing advantages and shortcomings of thoracic radiography.